2018
DOI: 10.1248/bpb.b17-00547
|View full text |Cite
|
Sign up to set email alerts
|

Association between Concomitant Use of Acyclovir or Valacyclovir with NSAIDs and an Increased Risk of Acute Kidney Injury: Data Mining of FDA Adverse Event Reporting System

Abstract: Whereas nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used for the treatment of acute or chronic conditions where pain and inflammation are present. Due to the current use profile of NSAIDs, either as prescription or OTC drugs, NSAIDs are likely to be used concomitantly with acyclovir or valacyclovir in clinical practice such as rheumatoid arthritis and herpes zoster virus infection, while the study on the safety of such combinations was hardly reported.It is known that both oral acyclovir (or val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Therefore, AKI risk evaluation for analgesics in concomitant use with VACV is needed. In previous studies, Yue et al (2014), Yue et al (2018) found that concomitant use of VACV and NSAIDs might increase AKI risk. However, the risk of AKI with concomitant use of acetaminophen remains unclear.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, AKI risk evaluation for analgesics in concomitant use with VACV is needed. In previous studies, Yue et al (2014), Yue et al (2018) found that concomitant use of VACV and NSAIDs might increase AKI risk. However, the risk of AKI with concomitant use of acetaminophen remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Analgesics such as nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently administered alongside VACV to treat pain related to herpes zoster. However, some NSAIDs have been shown to be associated with increased risk of VACV-related AKI in the FDA spontaneous reporting system (Yue et al, 2014; Yue et al, 2018). Acetaminophen, an analgesic, is generally regarded as safer than NSAIDs with regard to kidney function (Griffin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of NSAIDs with methotrexate could result in serious toxicity, including an increased risk of nephrotoxicity [ 48 , 49 ]. An increased risk of acute kidney injury was also observed with the concomitant use of NSAIDs with acyclovir or valacyclovir (a prodrug of acyclovir) [ 20 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…JADER has been utilized in many retrospective studies, [1][2][3] playing a major role in the safety evaluation of drugs in clinical practice sites in Japan. 4) The U.S. Food and Drug Administration (FDA) opened the FDA's Adverse Event Reporting System (FAERS) to the public, which is also a spontaneous adverse event report database similar to JADER. 5,6) This system was started in 1996, and data from more than 7 million reports have been collected from the U.S. and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting adverse event signals by data mining of the adverse reaction reports accumulated in these databases will enable the clarification of the incidence of adverse drug events. 4) The aim of this study was to evaluate the expression time of ganciclovir-induced adverse events by data mining of the adverse reaction reports, JADER, and FAERS. For this purpose, the number of reported cases of the main adverse reactions (cytopenia, leukopenia, thrombocytopenia, liver damage, and acute renal failure) of ganciclovir in JADER and FAERS were surveyed, and the incidence of these adverse reactions due to ganciclovir and their expression time were evaluated.…”
Section: Introductionmentioning
confidence: 99%